Diet-dependence of metabolic perturbations mediated by the endocrine disruptor tolylfluanid - Regnier, Shane M (Endocr Connect, 2017)
Emerging evidence implicates environmental endocrine-disrupting chemicals (EDCs) in the pathogenesis of metabolic diseases such as obesity and diabetes; however, the interactions between EDCs and traditional risk factors in disease pathogenesis remain incompletely characterized. The present study interrogates the interaction of the EDC tolylfluanid (TF) and traditional dietary stressors in the promotion of metabolic dysfunction. Eight-week-old male C57BL/6 mice were fed a high-fat, high-sucrose diet (HFHSD) or a high-sucrose diet (HSD), with or without TF supplementation at 100 μg/g, for 12 weeks. Food intake, body weight and visceral adiposity were quantified. Glucose homeostasis was interrogated by intraperitoneal glucose and insulin tolerance tests at 9 and 10 weeks of exposure, respectively. After 12 weeks of dietary exposure, metabolic cage analyses were performed to interrogate nutrient handling and energy expenditure. In the background of an HFHSD, TF promoted glucose intolerance; however, weight gain and insulin sensitivity were unchanged, and visceral adiposity was reduced. In the background of an HSD, TF increased visceral adiposity; however, glucose tolerance and insulin sensitivity were unchanged, while weight gain was reduced. Thus, these analyses reveal that the metabolic perturbations induced by dietary exposure to TF, including the directionality of alterations in body weight gain, visceral adiposity and glucose homeostasis, are influenced by dietary macronutrient composition, suggesting that populations may exhibit distinct metabolic risks based on their unique dietary characteristics.